Evaluating the efficacy of context-focused intervention in improving performance of functional tasks in preschool children with central nervous system dysfunction - Paithankar, Anushka B.; Jaywant, Shailaja S. (International Journal of Contemporary Pediatrics, 2018)
Background: Children with central nervous dysfunction should be given a variety of long-term physical and occupational therapy interventions to facilitate their self-development and to enhance functional independence in movement, self-care, play, school activities and leisure. The present study aimed to investigate the benefit of implementing context-focused intervention approach along with occupational therapy intervention in children with CNS dysfunctions. Methods: This randomized case control study conducted in 30 children with CNS dysfunction aging between 12 months to 48 months were randomly divided into control and experimental groups consisting of 15 children in each group. Control group received conventional occupational therapy for 45 min, and experimental group received context-focused intervention approach for 30 min along with conventional occupational therapy for 15 min (thrice a week). The patients were evaluated at baseline, after 12 and 24 weeks of follow up period on Canadian occupational performance measure (COPM) to evaluate parental perception about intervention, GMFM (gross motor function measure) to study the motor ability of the patient and ICF-CY (International classification of functioning, disability and health for children and youth) for activity participation and performance with evaluation of context. Results: Significant progress in the satisfaction score during 2nd and 3rd follow ups were noted (p <0.001) in experimental group. All the activities in GMFM score except lying and rolling showed significant improvement in experimental group (p <0.001). In experimental group a significant improvement in performance qualifier of ICF was seen during follow ups (p<0.001). The capacity qualifier scoring of ICF was improved in experimental group during 2nd follow up (p = 0.006). Progress in environmental scores of ICF during all the follow ups was noted (p <0.001) in experimental group. Significant correlation in GMFM scores and COPM performance score was noted during last follow-up in both the groups. Conclusions: The findings of the study showed positive results with context focused therapy and thus can be inferred that new intervention approach context focused therapy along with the conventional occupational therapy is very effective in improving the performance of functional tasks in children with CNS dysfunction.